Dampak Iklan Djarum Super Mild terhadap Psikologis Penonton di Televisi - Brizita Auliani Alwanda; Arfian Suryasuciramdhan; Helena Angelika Simbolon; Ratu Reva Nabila; Dian Hardianti Rukmanah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This ponder employments a semiotic and communication approach to look at the mental affect of the Djarum Super MLD cigarette notice broadcast on tv at night. The Djarum Super MLD cigarette promotion utilizes visual components set in remote scenes, and abnormal sound. The coasting scenes over water employing a flying board and the sound of disobedient considered unpleasant, particularly due to its airing time at night when the group of onlookers may feel lazy or half-conscious, causes an impact (liminality), which can cruel a position between two spaces or times, making encounters that regularly feel outside or awkward. Employing a subjective clear strategy based on writing investigate, this think about illustrates how the Djarum Super MLD cigarette notice influences the brain research of watchers from visual, sound, and airing time angles. The comes about show that cigarette notices are not as it were publicizing devices but moreover typical communication devices that can impact the mental state and contemplations of its gathering of people.